The girl on the train eaudiobook - Hawkins, Paula (Penguin Audio, 2015)
The #1  New York Times  Bestseller, USA Today Book of the Year, now a major motion picture.   The debut psychological thriller that will forever change the way you look at other people's lives.   “Nothing is more addicting than  The Girl on the Train. ”— Vanity Fair “ The Girl on the Train  has more fun with unreliable narration than any chiller since  Gone Girl . . . . [It] is liable to draw a large, bedazzled readership.”— The New York Times   “Marries movie noir with novelistic trickery. . . hang on tight. You'll be surprised by what horrors lurk around the bend.”— USA Today   “Like its train, the story blasts through the stagnation of these lives in suburban London and the reader cannot help but turn pages.”— The Boston Globe “ Gone Girl  fans will devour this psychological thriller.”— People       EVERY DAY THE SAME Rachel takes the same commuter train every morning and night. Every day she rattles down the track, flashes past a stretch of cozy suburban homes, and stops at the signal that allows her to daily watch the same couple breakfasting on their deck. She’s even started to feel like she knows them. Jess and Jason, she calls them. Their life—as she sees it—is perfect. Not unlike the life she recently lost. UNTIL TODAY And then she sees something shocking. It’s only a minute until the train moves on, but it’s enough. Now everything’s changed. Unable to keep it to herself, Rachel goes to the police. But is she really as unreliable as they say? Soon she is deeply entangled not only in the investigation but in the lives of everyone involved. Has she done more harm than good?